Brown's introduction to organic chemistry - Brown, William Henry; Poon, Thomas (John Wiley & Sons, 2018)
The text illustrates the use of organic chemistry as a tool in these sciences; it also stresses the organic compounds, both natural and synthetic, that surround us in everyday life: in pharmaceuticals, plastics, fibers, agrochemicals, surface coatings, toiletry preparations and cosmetics, food additives, adhesives, and elastomer.